Probiotics, prebiotics, and synbiotics - de Vrese, Michael; Schrezenmeir, J (Advances in biochemical engineering/biotechnology, 2008)
According to the German definition, probiotics are defined viable microorganisms, sufficient amounts of which reach the intestine in an active state and thus exert positive health effects. Numerous probiotic microorganisms (e.g. Lactobacillus rhamnosus GG, L. reuteri, bifidobacteria and certain strains of L. casei or the L. acidophilus-group) are used in probiotic food, particularly fermented milk products, or have been investigated--as well as Escherichia coli strain Nissle 1917, certain enterococci (Enterococcus faecium SF68) and the probiotic yeast Saccharomyces boulardii--with regard to their medicinal use. Among the numerous purported health benefits attributed to probiotic bacteria, the (transient) modulation of the intestinal microflora of the host and the capacity to interact with the immune system directly or mediated by the autochthonous microflora, are basic mechanisms. They are supported by an increasing number of in vitro and in vivo experiments using conventional and molecular biologic methods. In addition to these, a limited number of randomized, well-controlled human intervention trials have been reported. Well-established probiotic effects are: 1. Prevention and/or reduction of duration and complaints of rotavirus-induced or antibiotic-associated diarrhea as well as alleviation of complaints due to lactose intolerance. 2. Reduction of the concentration of cancer-promoting enzymes and/or putrefactive (bacterial) metabolites in the gut. 3. Prevention and alleviation of unspecific and irregular complaints of the gastrointestinal tracts in healthy people. 4. Beneficial effects on microbial aberrancies, inflammation and other complaints in connection with: inflammatory diseases of the gastrointestinal tract, Helicobacter pylori infection or bacterial overgrowth. 5. Normalization of passing stool and stool consistency in subjects suffering from obstipation or an irritable colon. 6. Prevention or alleviation of allergies and atopic diseases in infants. 7. Prevention of respiratory tract infections (common cold, influenza) and other infectious diseases as well as treatment of urogenital infections. Insufficient or at most preliminary evidence exists with respect to cancer prevention, a so-called hypocholesterolemic effect, improvement of the mouth flora and caries prevention or prevention or therapy of ischemic heart diseases or amelioration of autoimmune diseases (e.g. arthritis). A prebiotic is "a selectively fermented ingredient that allows specific changes, both in the composition and/or activity in the gastrointestinal microflora that confers benefits upon host well being and health", whereas synergistic combinations of pro- and prebiotics are called synbiotics. Today, only bifidogenic, non-digestible oligosaccharides (particularly inulin, its hydrolysis product oligofructose, and (trans)galactooligosaccharides), fulfill all the criteria for prebiotic classification. They are dietary fibers with a well-established positive impact on the intestinal microflora. Other health effects of prebiotics (prevention of diarrhoea or obstipation, modulation of the metabolism of the intestinal flora, cancer prevention, positive effects on lipid metabolism, stimulation of mineral adsorption and immunomodulatory properties) are indirect, i.e. mediated by the intestinal microflora, and therefore less-well proven. In the last years, successful attempts have been reported to make infant formula more breast milk-like by the addition of fructo- and (primarily) galactooligosaccharides.